Smart Sustainable Cities Profile: Podgorica, Montenegro - United Nations Economic Commission for Europe (United Nations, 2024)
The Smart Sustainable City Profile of Podgorica was developed based on the results of the evaluation of the performance of the city against the Key Performance Indicators for Smart Sustainable Cities. This City Profile includes an analysis of the outcomes of the evaluation, information on the city’s policies, programmes projects and partnerships that aim to accelerate the city’s progress towards achieving the SDGs, as well as policy recommendations for consideration of the city government.